Dental care in patients with epilepsy: a survey of 82 patients and their attending dentists and neurologists in southern Germany. (3rd September 2016) - Schöpper, Malin; Ludolph, Albert C.; Fauser, Susanne
Abstract : Introduction: The current study assessed the knowledge and attitudes of dentists and neurologists, and of their patients with epilepsy, in the catchment area of an outpatient clinic for epilepsy in southern Germany. Methods: One‐hundred patients with epilepsy were asked to complete questionnaires about their dental treatment. Attitudes of their attending dentists and neurologists were also assessed. Results: Patients with epilepsy: The questionnaires were returned by 82% of patients. Of these, 84% regularly (once or twice a year) sought out a dentist, 79% reported their epilepsy to the dentist, 6% were refused treatment by a dentist because of their epilepsy, 10% had already experienced a seizure while at a dental office and 52% wished for more detailed information pretreatment. Dentists: Although 97% treated patients with epilepsy, 21% believed that their equipment was inappropriate for treating a patient experiencing seizures. The majority were not familiar with interactions between antibiotics/analgetics and anti‐epileptic drugs. Short‐term general anaesthesia was preferred for critical patients by 70% of dentists, 70% recommended dental ceramic for prosthetic reconstruction of anterior teeth and 64% would not recommend use of a removable denture. Neurologists: Sixty‐two per cent were asked for advice by their patients, 71% knew about particular risks and interactions between antibiotics/analgetics and anti‐epileptic drugs, 8% would stop valproic acid before extensive dental intervention and 92% recommended general anaesthesia in critical patients (uncooperative patients, patients with learning difficulties, and patients with frequent generalised tonic‐clonic or complex partial seizures). Discussion: In general, patients were satisfied with their dental treatment. Regarding the clinician's role, however, dentists need to know more with respect to treating patients with seizures. Beyond that, it would be desirable for neurologists to take more time to answer their patients' questions regarding dental care.